Spatial distributions of intensive soybean, maize, and wheat - Guo, Zhe; You, Liangzhi; Zhang, Wei (2022)
Zhe Guo, Liangzhi You, Wei Zhang WEBINAR Enhancing Biodiversity and Resilience in Intensive Farming Systems: Results from an ETH Zürich-IFPRI Collaborative study Co-organized by IFPRI, ETH Zürich, and Bayer DEC 6, 2022 - 10:00 TO 11:30AM EST